Wood finishing and home furnishing - Ward, Catherine N. (My University, 1907)
Introduction: The growth in popular favor of bare wood floors is a part of the sensible movement for beauty, simplicity and utility in home decoration. Always the owner of a polished floor takes pride in it. Not the pride one would take in a beautiful rug or carpet. But a floor usually is treated under the supervision of the owner who watches it grow into a thing of beauty, and with increasing pleasure observes it gain new mellow luster as the years go by. It is a personal possession, a personal triumph, and a thing of which to feel justly proud. The housekeeper who is to care for these floors should have a thorough understanding of their treatment. In order to obtain any degree of excelency it is necessary to gain as much knowledge as possible of the materials used for furniture, floors and woodwork. They may be classified into two groups, the Hardwood, and Soft wood. Oak, ash, maple, walnut, mahogany, cherry and beech being classed as hard wood and white pine, yellow pine, hard pine, spruce, poplar, birch, and bass-wood as soft wood. Woods differ greatly in wearing quality; those which have a resinous substance well distributed throughout its structure do not decay when exposed to the weather as do the woods containing a soluble gum. It is better to use a wood that has had the sap soaked out of it than that which has been dried with the sap in the tissue, as moisture will have a decaying effect.
Citation: Ward, Catherine N. Wood finishing and home furnishing. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Hardwoods; Soft woods; Wood finishes; Home furnishings; Theses